2020
DOI: 10.1111/edt.12622
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the long‐term hospitalization of bicyclists and motorcyclists with oral and maxillofacial injuries

Abstract: Background/Aim Because bicyclists and motorcyclists with oral and maxillofacial injuries often suffer from disabilities requiring long‐term treatment, reducing the severity of such injuries is a valuable objective for improving these people's quality of life (QOL). The aims of this study were, first, to present the prevalence and patterns of oral and maxillofacial injuries of bicyclists and motorcyclists and to compare the features of these injuries and, second, to determine the factors contributing to long‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…Patients with cosmetic defects had higher scores of PTSD-related depression at different times. [30][31][32][33] In the present study, MFI significantly increased the likelihood of pain compared to the N-MFI group. Previous studies also reported severe pain from these types of injuries, which is one of the primary determinants of overall human function.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Patients with cosmetic defects had higher scores of PTSD-related depression at different times. [30][31][32][33] In the present study, MFI significantly increased the likelihood of pain compared to the N-MFI group. Previous studies also reported severe pain from these types of injuries, which is one of the primary determinants of overall human function.…”
Section: Discussionmentioning
confidence: 76%
“…A similar study reported that the recovery time from depression after MFI, which had only functional defects, was shorter compared with injuries with cosmetic defects. Patients with cosmetic defects had higher scores of PTSD‐related depression at different times 30–33 …”
Section: Discussionmentioning
confidence: 99%
“…These may be overlooked or disregarded due to the severity of the facial injuries 12 . Finally, the long‐term outcomes of MFI include substantial morbidity, deformity, loss of function, and high treatment cost 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…However, understanding the prevalence, etiology, severity, and temporal distribution of MFI in trauma may dictate efforts to reduce the burden of these injuries. Although the complexity of MFI management in the short‐term aftermath of the injury has been thoroughly documented, data on the long‐term disabilities and implications of maxillofacial trauma are limited 13,14 . The aim of this study was to characterize the patterns, associated injuries, and complications among a cohort of Israel Defense Forces (IDF) soldiers who suffered maxillofacial trauma along the continuum of care from pre‐hospital management through the hospital stay and long‐term follow‐up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation